Accelerated partial breast irradiation: a new standard of care? - Forster, Tobias; Köhler, Clara Victoria Katharina; Debus, Jürgen; Hörner-Rieber, Juliane (Breast care, 2020)
Background: Breast-conserving therapy including lumpectomy and adjuvant whole breast irradiation (WBI) has become the standard therapy for early-stage breast cancer (EBC). Without WBI, the recurrence rate is significantly increased. However, when selecting patients at a low a priori risk of local recurrence only a small breast-cancer-specific mortality benefit, but no overall survival improvement, was detected for WBI. As most recurrences occur close to the lumpectomy cavity, accelerated partial breast irradiation (APBI) delivered exclusively to a limited volume of tissue around the initial lumpectomy site, has gained increased attention and is now discussed as an alternative to WBI for selected EBC patients. Summary: Numerous techniques for APBI (interstitial brachytherapy, external beam-based APBI, intraoperative radiotherapy, MR-guided radiotherapy) allow treatment delivery in a shorter period of time, and radiation oncologists expect to further reduce side effects by using these new techniques, with improvements in cosmetics and quality of life. In this review, we aim to describe the existing evidence for the feasibility and effectiveness of different APBI techniques used in modern radiotherapy. Key Messages: APBI has provided outcomes similar to WBI combined with potentially reduced toxicity. While appropriate patient selection persists to be crucial for acceptable recurrence rates, the precise definition of patients suitable for APBI remains a matter of discussion. As long-term data are often still lacking, special attention should be paid to late side effects and long-term outcomes. Decision-making on appropriate treatment techniques should take into account not only local control rates, but also the impact on the patient’s quality of life.